Enhanced Recognition of HIV-1 Cryptic Epitopes Restricted by HLA Class I Alleles Associated With a Favorable Clinical Outcome. (1st September 2015) - Bansal, Anju; Mann, Tiffanie; Sterrett, Sarah; Peng, Binghao J.; Bet, Anne; Carlson, Jonathan M.; Goepfert, Paul A.
Abstract : Background: Cryptic epitopes (CEs) are peptides derived from the translation of 1 or more of the 5 alternative reading frames (ARFs; 2 sense and 3 antisense) of genes. Here, we compared response rates to HIV-1–specific CE predicted to be restricted by HLA-I alleles associated with protection against disease progression to those without any such association. Methods: Peptides (9mer to 11mer) were designed based on HLA-I–binding algorithms for B*27, B*57, or B*5801 (protective alleles) and HLA-B*5301 or B*5501 (nonprotective allele) in all 5 ARFs of the 9 HIV-1 encoded proteins. Peptides with >50% probability of being an epitope (n = 231) were tested for T-cell responses in an IFN-γ enzyme-linked immunosorbent spot (ELISpot) assay. Peripheral blood mononuclear cell samples from HIV-1 seronegative donors (n = 42) and HIV-1 seropositive patients with chronic clade B infections (n = 129) were used. Results: Overall, 16%, 2%, and 2% of chronic HIV infected patients had CE responses by IFN-γ ELISpot in the protective, nonprotective, and seronegative groups, respectively ( P = 0.009, Fischer exact test). Twenty novel CE-specific responses were mapped (median magnitude of 95 spot forming cells/10 6 peripheral blood mononuclear cells), and most were both antisense derived (90%) and represented ARFs of accessory proteins (55%). CE-specific CD8 T cells were multifunctional and proliferated when assessed by intracellular cytokine staining. Conclusions: CE responses were preferentially restricted by the protective HLA-I alleles in HIV-1 infection, suggesting that they may contribute to viral control in this group of patients. Abstract : Supplemental Digital Content is Available in the Text.